Sex‐specific and caste‐specific brain adaptations related to spatial orientation in Cataglyphis ants. Issue 18 (9th August 2021) - Grob, Robin; Heinig, Niklas; Grübel, Kornelia; Rössler, Wolfgang; Fleischmann, Pauline N.
Abstract: Cataglyphis desert ants are charismatic central place foragers. After long‐ranging foraging trips, individual workers navigate back to their nest relying mostly on visual cues. The reproductive caste faces other orientation challenges, i.e. mate finding and colony foundation. Here we compare brain structures involved in spatial orientation of Cataglyphis nodus males, gynes, and foragers by quantifying relative neuropil volumes associated with two visual pathways, and numbers and volumes of antennal lobe (AL) olfactory glomeruli. Furthermore, we determined absolute numbers of synaptic complexes in visual and olfactory regions of the mushroom bodies (MB) and a major relay station of the sky‐compass pathway to the central complex (CX). Both female castes possess enlarged brain centers for sensory integration, learning, and memory, reflected in voluminous MBs containing about twice the numbers of synaptic complexes compared with males. Overall, male brains are smaller compared with both female castes, but the relative volumes of the optic lobes and CX are enlarged indicating the importance of visual guidance during innate behaviors. Male ALs contain greatly enlarged glomeruli, presumably involved in sex‐pheromone detection. Adaptations at both the neuropil and synaptic levels clearly reflect differences in sex‐specific and caste‐specific demands for sensory processing and behavioral plasticity underlying spatial orientation. Abstract : Cataglyphis desert ants show impressive navigation capabilities during foraging. The reproductive caste faces other orientation challenges. Here, we compare brain structures involved in spatial orientation of Cataglyphis nodus males (♂), gynes (♀), and foragers (☿) by quantifying relative neuropil volumes, synaptic architecture, and numbers and volumes of antennal lobe olfactory glomeruli. Adaptations at both the neuropil and synaptic levels clearly reflect differences in sex‐specific and caste‐specific demands for sensory processing and behavioral plasticity underlying spatial orientation.